The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d1ob02270a
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective catalytic Povarov reactions

Abstract: Catalytic asymmetric Povarov protocols have undergone an explosive growth, especially in the last ten years, since the first example was published in 1996. The use of chiral Lewis and Brønsted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…Asymmetric Povarov protocols have experienced significant growth in recent years. 100,108 Chen, Zhou, and co-workers described a CPA-catalyzed three-component Povarov reaction with subsequent DDQ oxidation to provide axially chiral quinoline-naphthalene compounds (Scheme 33). 109 The protocol started with imine formation between aniline and benzaldehyde derivatives, followed by the stereoselective (4 + 2) cycloaddition reaction with 1-styryl naphthols.…”
Section: Reviewmentioning
confidence: 99%
“…Asymmetric Povarov protocols have experienced significant growth in recent years. 100,108 Chen, Zhou, and co-workers described a CPA-catalyzed three-component Povarov reaction with subsequent DDQ oxidation to provide axially chiral quinoline-naphthalene compounds (Scheme 33). 109 The protocol started with imine formation between aniline and benzaldehyde derivatives, followed by the stereoselective (4 + 2) cycloaddition reaction with 1-styryl naphthols.…”
Section: Reviewmentioning
confidence: 99%
“…A Povarov reaction is a Diels–Alder reaction between an N -aryl imine and an electron-rich dienophile in the presence of Lewis acid as catalyst, used for the synthesis of quinolines [ 78 , 79 , 80 , 81 , 82 ]. The reaction is an inverse electron demand Diels–Alder (IEDDA).…”
Section: Synthetic Strategies For the Preparation Of Fused Pyridocoum...mentioning
confidence: 99%
“…4,5 Examples include the natural There are many synthetic routes to access chiral THQ, 5 but the simplest and most versatile to implement with a multicomponent approach remains the asymmetric Povarov reaction. 10,11 Synthesis of highly optically pure THQs can be achieved by enantioselective Povarov reactions based on a [4+2] cycloaddition or a Mannich/Friedel-Craft sequence mechanism. 4 The seminal work by Kobayashi and co-workers showed that trisubstituted THQ can be obtained in good enantioselectivity with a cis-2,3 and cis-3,4 configuration (Scheme 1, Eq.1).…”
Section: Introductionmentioning
confidence: 99%
“…There are many synthetic routes to access chiral THQ, [5] but the simplest and most versatile to implement with a multicomponent approach remains the asymmetric Povarov reaction [10,11] . Synthesis of highly optically pure THQs can be achieved by enantioselective Povarov reactions based on a [4+2] cycloaddition or a Mannich/Friedel‐Craft sequence mechanism [4] .…”
Section: Introductionmentioning
confidence: 99%